Control Variables: A Review and Proposed Guidelines - Memon, Mumtaz Ali (Journal of Applied Structural Equation Modelling, 2024)
Although considerable research on control variables offers best practice recommendations, there are still shortcomings in their application. A significant proportion of quantitative studies lack rigor in how they apply control variables. Additionally, existing literature on control variables is primarily technical, with a noticeable lack of accessible guidance that could benefit both seasoned and novice researchers. In fact, there is a need for more elaboration in non-technical terms to enhance our understanding of using control variables effectively. The objectives of this editorial are twofold: First, we elaborate on five key issues related to control variables, including a clear, easy-to-understand explanation of what a control variable is, their advantages and complications, and the issues associated with under- or over-controlling variables. Second, we provide guidelines that are easy to follow for any researcher, whether experienced or novice. In doing so, we clarify several ambiguities and offer straightforward explanations of issues related to control variables. We hope that this effort will assist researchers—whether lecturers or students—by providing clear directions on the appropriate use of control variables.